Development and Application of RAA Nucleic Acid Test Strip Assay and Double RAA Gel Electrophoresis Detection Methods for ASFV and CSFV - Wu, Keke; Zhang, Yuanyuan; Zeng, Sen; Liu, Xiaodi; Li, Yuwan; Li, Xiaowen; Chen, Wenxian; Li, Zhaoyao; Qin, Yuwei; Chen, Jinding; Fan, Shuangqi (Frontiers in Molecular Biosciences, 2022)
African swine fever（ASF）is an acute, severe and hemorrhagic infectious disease caused by African swine fever virus (ASFV) infecting domestic pigs and wild boars. Since the outbreak of the disease in China in 2018, it has brought a great impact on China's pig industry. Classical swine fever (CSF) is an acute contact infectious disease of pigs caused by classical swine fever virus (CSFV) infection. Clinically, acute CSF usually shows high fever missed, anorexia, extensive congestion and bleeding of the skin and mucosa, which are similar to ASF. It is of great significance to prevent, control and accurately detect ASF and CSF in pig farms. In this study, Recombinase aided amplification (RAA) technology combined with a nucleic acid test strip (RAA-strip) was established for simple and specific detection of ASFV/CSFV. The sensitivity and preliminary clinical application results showed that the RAA test strip established in this study could detect recombinant plasmids containing ASFV/CSFV gene fragments as low as 103 copies/µL. The minimum detection limits of virus DNA/cDNA were 10 pg and 12 pg respectively, and there was no cross-reaction with other porcine viruses. The specificity of the method was good. We used 37-42 clinical samples to evaluate the performance of our established method, and the positive concordance rates with conventional PCR were 94.1% and 57.1%, respectively. In addition, ASFV and CSFV double RAA agarose gel electrophoresis detection methods were established. The results showed that the method had good specificity. The detection limit of this method is 106 copies for ASFV p72 gene recombinant plasmid and 105 copies for CSFV NS5B Gene recombinant plasmid. The use of this method for clinical material detection was consistent with the PCR method. In summary, the developed method of RAA-strip assay for ASFV and CSFV realized the visual detection of pathogens, and the developed method of dual RAA agarose gel electrophoresis assay for ASFV and CSFV realized the simultaneous detection of two pathogens in one reaction, with good specificity, high sensitivity and rapid reaction rate, which was expected to be clinically feasible for the differential diagnosis of ASF and CSF provided technical support.